(untitled) (Orfeu, 2024)
This article explores the role of ornamentation in contemporary musical practice, using Johann Sebastian Bach’s Suite No. 2 in D minor for cello (BWV 1008) as a case study. Based on observations by Carl Philipp Emanuel Bach and Daniel Leech-Wilkinson, the study analyzes 17 recordings by 13 different artists, spanning a period of 78 years, to understand how contemporary musicians approach ornamentation. The methodology involves a comparative analysis of recordings and written notation, highlighting the importance of attentive listening and studying past interpretations. It is concluded that ornamentation not only enriches musical expression but also reflects the creativity of the performer. The discussion on the pedagogy of ornamentation emphasizes the need for musicians to develop their own interpretative language rather than strictly adhering to historical conventions.